2009
DOI: 10.1002/jor.20818
|View full text |Cite
|
Sign up to set email alerts
|

Strontium–calcium coadministration stimulates bone matrix osteogenic factor expression and new bone formation in a large animal model

Abstract: Strontium (Sr) has become increasingly attractive for use in the prevention and treatment of osteoporosis by concomitantly inhibiting bone resorption and enhancing bone formation. Strontium shares similar chemical, physical, and biological characteristics with calcium (Ca), which has been widely used as a dietary supplement in osteoporosis. However, the effects of Sr-Ca coadministration on bone growth and remodeling are yet to be extensively reported. In this study, 18 ovariectomized goats were divided into fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 31 publications
3
22
0
Order By: Relevance
“…In addition, Ca sources such as coral sand increased RUNX2 and COL-1 mRNA expression [39]. Moreover, Sr-Ca co-administration upregulated RUNX2 mRNA expression [40]. These results provide important insights into how the downstream components of the BMP-2 signaling pathways, which we have identified as RUNX2 and receptor-activated SMADs and induce osteoblast differentiation in OVX rat (Figure 8).…”
Section: Discussionmentioning
confidence: 91%
“…In addition, Ca sources such as coral sand increased RUNX2 and COL-1 mRNA expression [39]. Moreover, Sr-Ca co-administration upregulated RUNX2 mRNA expression [40]. These results provide important insights into how the downstream components of the BMP-2 signaling pathways, which we have identified as RUNX2 and receptor-activated SMADs and induce osteoblast differentiation in OVX rat (Figure 8).…”
Section: Discussionmentioning
confidence: 91%
“…This Sr compound exerts a beneficial effect in a goat osteoporosis model by preventing trabecular bone deterioration. 13,14 Both Veh and Sr compound were orally administrated by gavage daily for 12 weeks starting immediately postoperatively. The dosage exerts anabolic effect on bone in mice and rats.…”
Section: Animal Treatmentmentioning
confidence: 99%
“…The expression of insulin-like growth factor (IGF)-1 and runt-related transcription factor 2 (Runx2) was significantly up-regulated within the treated group; tumour necrosis factor expression was also significantly down-regulated in that group [22]. Small animal models (rats) have demonstrated that BMSCs produced larger osteogenic colonies but smaller adipogenic colonies in Sr-treated OVX rats.…”
Section: Introductionmentioning
confidence: 96%